MICROFINANCE-ECONOMIC GROWTH NEXUS: A CASE STUDY ON GRAMEEN BANK IN BANGLADESH - Amin, Md. Fouad Bin; Uddin, Shah Jalal (Universitas Muhammadiyah Yogyakarta, 2018)
Microfinance is one of the fastest growing sectors in Bangladesh and in many parts of the world. Over the last few decades, this sector has been supportive in achieving various socio-economic goals in Bangladesh. The country has made remarkable progress in sectors like education and health, and most importantly it has contributed significantly in poverty alleviation. Although the microfinance mostly concentrates at the micro level, it has direct effect on the macro economy. A forefront Microfinance provider like Grameen Bank has been playing a key role for the socio-economic wellbeing of the people living in the rural areas as well as for the economic development of rural economy. This study aims to investigate the long run dynamic relationship among its loan financing and clients’ deposit and economic growth in Bangladesh. By considering annual time-series data of these variables, a widely used cointegration test and Granger’s causality test have been applied to examine the long run relationship among these variables. The result shows that both financing and depositing aspects of Grameen Bank have positive effect on economic growth of Bangladesh in the long run. It is recommended that Grameen Bank should allow its operations without any external pressure for the sake of sound economic growth of the country.